PERILAKU BERISIKO YANG MEMPENGARUHI TINGKAT RISIKO PENGGUNAAN NARKOTIKA PADA SISWA SMKN 1 SINGKAWANG - Azmiardi, Akhmad; Taufik, M; Abrori, Abrori (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2016)
Prevalence of drug abuse among students indicated continually increased each year. SMKN 1 Singkawang contributed the highest number of indicated students. There were 2 students in 2012, 1 student in 2013 and 2 students in 2014.This study aimed at finding out the risky behavior of the drug use among students of SMK N I Singkawang.Using analytic survey and cross sectional approach, as many as 278 out of 1008 students of grades X, XII, an XII were selected as the samples of this study. They were chosen by using proportional random sampling. The test used was chi square test, with 95% confidence level.The study revealed that there were significant correlation of smoking behavior (41,336 CI 95%=5,614-81,214 p=0,000) night club visiting behavior (RP=58,109, CI 95%= 10,622-577,838, p=0,00), hang out behavior (RP=9,853 CI 95%= 1,320-73,535, p = 0,007) skipping class behavior (RP=18,847 CI 95%=4,477-79,572), p = 0,000) and alcohol intake behavior (RP=86,894 CI 95%= 19,104-90,260) p= 0,000) .From the findings, the headmaster needs to have a collaboration with the Police Department / National Narcotics Board in socializing the dangers of drug abuse. Also, both head master and teachers are encouraged to be active in monitoring the students, discipline in teaching learning process.Keywords: narcotics, adolescents, the risk of drug use, risky behavior